The Physical Factors Affecting to Students Life in Higher-Education: A Case Study on Wheelchair-Bounded Students in a Private University - Sridara Tipian; Antika Sawadsri (My University, 2017)
There are 48.37% in Thailand, who use wheelchairs, but they can be learned. The percentage of the disabled who are in higher education system only 1.61%. The result of physical factors where are not ready. This research focused study of physical factors affecting to wheelchair-bounded student by qualitative research; survey, access audit and the semi-structured interview. Found that factors affecting are entrance, classroom, activities area and restroom. Enhancing technical knowledge to the building manager to responding to all usage. Contributors often avoid seeking help because don't want to feel like a burdensome. The most important is that family are another motive to study.
Keywords: Physical Education; Inclusion and Disability in Education and Sport